Differentiation of pancreatic epithelial progenitor cells into hepatocytes following transplantation into rat liver - Dabeva, Mariana D. (The National Academy of Sciences of the USA, 1997)
The ability to identify, isolate, and transplant progenitor cells from solid tissues would greatly facilitate the treatment of diseases currently requiring whole organ transplantation. In this study, cell fractions enriched in candidate epithelial progenitor cells from the rat pancreas were isolated and transplanted into the liver of an inbred strain of Fischer rats. Using a dipeptidyl dipeptidase IV genetic marker system to follow the fate of transplanted cells in conjunction with albumin gene expression, we provide conclusive evidence that, after transplantation to the liver, epithelial progenitor cells from the pancreas differentiate into hepatocytes, express liver-specific proteins, and become fully integrated into the liver parenchymal structure. These studies demonstrate the presence of multipotent progenitor cells in the adult pancreas and establish a role for the liver microenvironment in the terminal differentiation of epithelial cells of foregut origin. They further suggest that such progenitor cells might be useful in studies of organ repopulation following acute or chronic liver injury.